2017
DOI: 10.1016/j.tet.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A sequential cycloaddition strategy for the synthesis of Alsmaphorazine B traces a path through a family of Alstonia alkaloids

Abstract: Driven by a new biogenetic hypothesis, the first total synthesis of alsmaphorazine B and several related indole alkaloids has been achieved. Numerous early approaches proved unsuccessful owing to unproductive side reactivity; nevertheless, they provided important clues that guided the evolution of our strategy. Critical to our success was a major improvement in our Zincke aldehyde cycloaddition strategy, which permitted the efficient gram-scale synthesis of akuammicine. The sequential chemoselective oxidations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 103 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…29 We envisioned accessing the pentacyclic N-oxide 9 via chemoselective oxidation of vinylogous urethane (-)-10, an advanced intermediate used in our synthesis of kopsifolines A and E. Our synthesis of the key hexacyclic enamine 8 commenced with derivatization of vinylogous urethane (-)-10 (Scheme 2), a C21-oxygenated variant of tabersonine 37 that we have previously prepared in enantiomerically enriched form in ten steps from a readily available indole derivative. 29,36,38 We found that treatment of vinylogous urethane (-)-10 (90% ee) with peracetic acid (1.3 equiv) 29,39 provided the desired N9-oxidation (70%) while minimizing a competitive C3-oxidation. 40 Subsequent unveiling of the primary alcohol afforded the N-oxide alcohol 9 in 96% yield (Scheme 2).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…29 We envisioned accessing the pentacyclic N-oxide 9 via chemoselective oxidation of vinylogous urethane (-)-10, an advanced intermediate used in our synthesis of kopsifolines A and E. Our synthesis of the key hexacyclic enamine 8 commenced with derivatization of vinylogous urethane (-)-10 (Scheme 2), a C21-oxygenated variant of tabersonine 37 that we have previously prepared in enantiomerically enriched form in ten steps from a readily available indole derivative. 29,36,38 We found that treatment of vinylogous urethane (-)-10 (90% ee) with peracetic acid (1.3 equiv) 29,39 provided the desired N9-oxidation (70%) while minimizing a competitive C3-oxidation. 40 Subsequent unveiling of the primary alcohol afforded the N-oxide alcohol 9 in 96% yield (Scheme 2).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Our synthesis of the key hexacyclic enamine 8 commenced with the derivatization of vinylogous urethane (−)- 10 (Scheme ), a C21-oxygenated variant of tabersonine that we have previously prepared in enantiomerically enriched form in 10 steps from a readily available indole derivative. ,, We found that the treatment of vinylogous urethane (−)- 10 (90% ee) with peracetic acid (1.3 equiv) , provided the desired N9-oxidation (70%) while minimizing a competitive C3-oxidation . Subsequent unveiling of the primary alcohol afforded the N-oxide alcohol 9 in 96% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…This convenient route to tetracyclic skeleton 103 opened the way to the synthesis of naturally occurring and biologically important indole monoterpene alkaloids, such as (±)‐norfluorocurarine, (±)‐dehydrodesacetylretuline, (±)‐valparicine, and (±)‐strychnine. In 2017, the first total synthesis of (±)‐alsmaphorazine B and several related indole alkaloids were accomplished through this strategy as well …”
Section: Diels–alder Reactionsmentioning
confidence: 99%
“…In 2017, the first total synthesis of (AE)-alsmaphorazine Ba nd severalr elatedi ndole alkaloids were accomplished through this strategy as well. [36] Scheme9.An intramolecular Diels-Alder cycloaddition strategy to tetracyclic indoline 81 (Szµntay et al [32] ).…”
Section: Diels-alder Reactionsmentioning
confidence: 99%